2020
DOI: 10.3390/ijerph17239043
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Blood Lactate Levels on Cognitive Domains and Physical Health during a Sports Stress. Brief Review

Abstract: The present review aims to examine the effects of high blood lactate levels in healthy adult humans, for instance, after a period of exhaustive exercise, on the functioning of the cerebral cortex. In some of the examined studies, high blood lactate levels were obtained not only through exhaustive exercise but also with an intravenous infusion of lactate while the subject was immobile. This allowed us to exclude the possibility that the observed post-exercise effects were nonspecific (e.g., cortical changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…However, while the number of SARS-CoV-2 cases was higher in Veneto on 24 February, it then increased more rapidly and with more intensity in Emilia-Romagna and Piedmont. Although the government measures were effective to slow down the epidemic in all the Italian regions 5 , 6 , the comparison between cluster 1 and 2 corroborates that the earlier the measures were taken, the lower the cumulative incidence achieved 8 . Indeed, Veneto imposed regional measures of travel restrictions earlier than Emilia-Romagna and Piedmont 3 .…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…However, while the number of SARS-CoV-2 cases was higher in Veneto on 24 February, it then increased more rapidly and with more intensity in Emilia-Romagna and Piedmont. Although the government measures were effective to slow down the epidemic in all the Italian regions 5 , 6 , the comparison between cluster 1 and 2 corroborates that the earlier the measures were taken, the lower the cumulative incidence achieved 8 . Indeed, Veneto imposed regional measures of travel restrictions earlier than Emilia-Romagna and Piedmont 3 .…”
Section: Discussionmentioning
confidence: 55%
“…Indeed, after modelling Italy as a network of regions, the authors concluded that intermittent regional strategies might avoid saturation of regional health systems and mitigate the economic impact 10 . In a recent work, we proposed that the classification of Italian regions into different clusters could have supported the development of specific strategies after the Italian national lockdown 14 . In part this happened after 6 November 2020, when a governmental decree classified Italian regions and autonomous provinces into three areas—red, orange, and yellow—which corresponded to three different risk scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies show higher concentrations of lactate in women with FM, both at rest [ 47 ] and after exercise [ 48 ]. However, the role of lactate, as well as other variables related to intense physical activity, is still intriguing [ 49 ]. Exercise-induced pain [ 9 ], in addition to high lactate levels [ 19 ], might be a reason to why women with FM prefer exercises generating lower ratings of perceived exhaustion [ 24 , 46 ] even though the relationship between physical activity and central pain processing is less clear in patient populations [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies highlighted the negative effect of exhausting exercise on postural control in upright stance [7][8][9]. When an individual performed a maximal exercise, a fast decrease in muscle phosphocreatine has been observed, as well as an accumulation of metabolites like lactate [10,11], influencing the normal functioning of several brain structures [12,13], such as the primary motor cortex and the supplementary motor area [14,15] obviously involved in human walking [16][17][18]. As aforementioned, postural control describes the way our central nervous system regulates sensory information from other systems (visual, vestibular, and somatosensory) in order to produce adequate motor output to maintain a controlled balance.…”
Section: Introductionmentioning
confidence: 99%